Review of the Fossil Heritage Potential of Shenzhen (Guangdong, China): A Promising Area for Palaeontological Research - David Marius Kroeck; Yanxin Gong; He Chen; Lan Li; Tong Bao (Geosciences)
The area of the city of Shenzhen at the Pearl River Delta in Guangdong Province, China, comprises rocks that preserve, with few interruptions, around 1.8 billion years of geological history. However, to date, only few scientific studies within a palaeontological context have been conducted on the sediment rocks in Shenzhen. Herein, the fossil record and heritage potential of Shenzhen is reviewed. The few existing previous investigations revealed a rich terrestrial and marine fossil record and show the great potential of this area for future palaeontological research, particularly on the upper Palaeozoic and Mesozoic strata: Carboniferous successions show plant remains and a diverse benthic marine fauna; fossils from Upper Triassic–Middle Jurassic sediment rocks provide important data for terrestrial and marine palaeoecosystems of this time; and the discovery of dinosaur nests in the Upper Cretaceous strata complements the previously known distribution of dinosaurs in South China. Additionally, micropalaeontological and palynological data from the upper Palaeozoic as well as Cenozoic successions in Shenzhen reveal diverse assemblages of foraminifera, ostracods, diatoms, and sporomorphs. Moreover, fossil finds in equivalent rocks in adjacent areas indicate great potential for the units in the Shenzhen area, in which, so far, no fossils have been found.